Progressive back-warping of a rider block atop an actively exhuming, continental low-angle normal fault. (January 2020) - Webber, S.; Little, T.A.; Norton, K.P.; Österle, J.; Mizera, M.; Seward, D.; Holden, G.
Abstract: Can continental low-angle normal faults (LANFs) initiate and remain active at shallow (<30°) dips? The Mai'iu-Gwoira fault system is an active, large-displacement detachment fault in SE Papua New Guinea. Although the Mai'iu fault is still active in the west, to the east it dips 15–22° at the surface, and has been abandoned in favor of the younger, 42 ± 7° dipping Gwoira fault. Fault abandonment has caused part of the former hanging wall to be captured by the footwall. This rider block's structure records progressive shallowing of the Mai'iu fault concurrent with slip. We present 26 Al/ 10 Be cosmogenic nuclide burial dating; along with a recently published (U–Th-Sm)/He apatite and zircon age, these provide the first direct dating of the Gwoira conglomerate. These data imply inception of the Mai'iu fault before 3.12–6.04 Ma, and inception of the Gwoira fault between 2.29 and 5.62 Ma. Bedding fault cut-off angles suggest the Mai'iu fault did not initiate as a LANF. Rather, it initially dipped >44° at the surface, and was subsequently back-rotated while active to its present 15–22° surface dip. This suggests that continental LANFs initiate at moderate dips, and evolve according to the 'rolling-hinge' process. Highlights: A low-angle normal fault in SE PNG initiated with a >44° 'Andersonian' surface dip. The dip of the fault decreased as slip proceeded. Part of the fault was abandoned, resulting in the development of a rider block. The rider block was rotated as slip proceeded, and preserves sedimentary dip-fanning. 10 Be/ 26 Al cosmogenic burial dating of rider block sediments provide age constraints.